Marginal fit of nickel-chromium copings before and after internal adjustments with duplicated stone dies and disclosing agent. - Ushiwata, O.; de Moraes, J. V.; Bottino, M. A.; da Silva, E. G. (Elsevier, 2000)
STATEMENT OF PROBLEM: Despite careful procedures, master stone dies may be damaged during laboratory procedures. The dentist routinely adjusts castings because the marginal fit of casting is not as accurate as on the dies. PURPOSE: This study evaluated the technique of internal adjustment of castings with use of duplicated stone dies and a disclosing agent to improve marginal fit discrepancy. MATERIAL AND METHODS: Thirty-two nickel-chromium copings were fabricated and simulated standard clinical and laboratory procedures with 2 variables: tooth preparation convergence angles of 6 and 18 degrees, with or without internal relief. Master stone dies and their duplicates were selected for coping construction and internal adjustment, respectively. A specimen positioning device was coupled with a Toolmakers microscope to allow reproducibility of measurements. Each coping was evaluated at 8 locations of its marginal perimeter, before and after internal adjustment. RESULTS: Marginal fit discrepancy of copings were significantly reduced with an internal adjustment technique (mean > 52%) for all experimental groups. Tooth preparations with greater convergence and internally relieved castings recorded a better marginal fit. CONCLUSION: The casting internal adjustment technique with use of duplicated stone dies and a disclosing agent substantially reduced marginal fit discrepancy.
Keywords: calcium sulfate; chromium derivative; coloring agent; diagnostic agent; analysis of variance; chemistry; comparative study; dental care; dental impression; denture; endodontics; human; in vitro study; statistics; tooth crown; Analysis of Variance; Calcium Sulfate; Chromium Alloys; Coloring Agents; Crowns; Dental Abutments; Dental Casting Technique; Dental Impression Technique; Dental Models; Humans; Marginal Adaptation (Dentistry)